Interação térmica entre edifícios inseridos na malha urbana verticalizada do bairro de Boa Viagem na cidade do Recife-PE - Bittencourt, Sérgio Motta (2006)
This dissertation aims to investigate the nature of the thermal interaction between two close-facing buildings, within the urban verticalized context of the area of Boa Viagem, Recife-PE. The method adopted consisted of hourly measurements of air temperature, relative humidity, wind direction and speed through five meteorological stations installed in the confronting façades of the two buildings. In the same period, at eight points throughout the day, measurements of superficial temperature of these façades and floors between the buildings has been carried out; including radiating temperature measured through a globe thermometer located between the two buildings. For analysis of the thermal distribution of the façades, infra red images were used. The data captured has been compared with the data taken from the meteorological station at the local airport, (reference station), and analyzed using the Pearson method of statistics analysis. The results show that the mean temperature of the façades and air between the buildings are highly influenced by the direct solar radiation, as well as by the reflection of the solar radiation and emission of long-wave radiation, through the façade of the confronting building and floor between them. It was also observed that the colors of the façades and constitution of the walls affect the temperature of the façades. Comparison with the data of the reference station showed an accented reduction of the mean wind speed and increase of the mean air temperature, with formation of urban heat island between the buildings. Thus, the current model of urban planning adopted in the studied area is not the most adequate bioclimatic solution, because it is condusive to the formation of a heat island between buildings.